Identitas Pemuda Kelompok Seni Paijo - Mochammad Fiki Eko Syahputra Yudhoyono; Rizqi Ahmad Muzaki; Alvina Setiyawati; Dhiyaul Haqqi Al-Mumtaza (Institut Nalanda, 2025)
This article discusses the Paijo art group as a medium for the formation and expression of the identity of today’s youth or Generation Z through the arts, especially in the field of theater. The shift from the New Order to the Reform Era has created an atmosphere that can lead youth to lose direction in their quest for identity. During the New Order era,